Do Friends Help Us in The Learning Process?; STAD Method Implementation to Boost Students’ Understanding of English Text - Syaefani Arif Romadhon; Muchammad Sofyan Firmansyah; Nawangsih Edynna Putri (English Language Education Department, Universitas Majalengka, 2024)
This research aimed to determine the effect of the application of the Student Teams-Achievement Divisions (STAD) learning method on students' reading skills. The research design used was a one-group pretest-posttest design. The sample consisted of 40 vocational high school students. Data were collected through pretest, posttest, and group tests. Data analysis used paired t-test and one-way ANOVA. The results of the analysis showed that students' reading scores significantly increased after the application of the STAD method. The mean score of the pretest was 70.2, increasing to 82.4 in the posttest, and 85.1 in the group test. A paired t-test revealed significant differences between the pretest and posttest (p<0.01), while an ANOVA test also showed significant differences among the three measurements (p<0.01). The increase in scores from the pretest to the posttest by 12.2 points, as well as the higher group test score than the posttest, indicated the effectiveness of the STAD method in improving students' reading ability and good knowledge retention.